Saving Cape Hatteras Lighthouse from the Sea: Options and Policy Implications (The National Academies Press, 1988)

Future of the National Weather Service Cooperative Observer Network - National Research Council (The National Academies Press, 1998)
Keywords: Earth Sciences

An Assessment of the Advanced Weather Interactive Processing System: Operational Test and Evaluation of the First System Build - National Research Council (The National Academies Press, 1997)
Keywords: Earth Sciences

A Vision for the National Weather Service: Road Map for the Future - National Research Council (The National Academies Press, 1999)
In this study, the committee explores ways the National Weather Service (NWS) can take advantage of continuing advances in science and technology to meet the challenges of the future. The predictions are focused on the target year 2025. Because specific predictions about the state of science and technology or the NWS more than 25 years in the future will not be entirely accurate, the goal of this report is to identify and highlight trends that are most likely to influence change. The Panel on the Road Map for the Future National Weather Service developed an optimistic vision for 2025 based on advances in science and technology.
Keywords: Earth Sciences

Statistics and Physical Oceanography (The National Academies Press, 1993)
Keywords: Earth Sciences

Beach Nourishment and Protection (The National Academies Press, 1995)
Many coastal communities have built structures at their beaches and added quantities of sand in contoured designs to combat erosion. Are such beach nourishment projects technically and economically sound? Or are they nothing more than building sand castles, as critics claim? Beach Nourishment and Protection provides a sound technical basis for decision-making, with recommendations regarding the utility of beach nourishment, the appropriate role of federal agencies, responsibility for cost, design methodology, and other issues. This volume: Examines the economic and social role of beaches, the history of beach nourishment projects, and management strategies for shore protection. Discusses the role of the U.S. Army Corps of Engineers and other federal agencies, with a close-up look at the federal flood insurance program. Explores the state of the art in project design and prediction of outcomes, including the controversy over the use of traditional and nontraditional shore protection devices. Addresses what is known about the environmental impacts of beach nourishment. Identifies what outcomes should be targeted for continued monitoring by project officials. Beach Nourishment and Protection provides insight into the technical, economic, environmental, and policy implications of beach nourishment and protection, with examples and suggested research directions.
Keywords: Earth Sciences

Review of the Draft Plan for the Modernization and Associated Restructuring Demonstration - National Research Council (The National Academies Press, 1999)
The public law that authorized the National Weather Service (NWS) to modernize its technical systems and restructure its field office organization set the requirements for what has become known as the modernization and associated restructuring demonstration (MARD). The law requires testing of the integrated performance, over a sustained period, of the modernized components and an operational demonstration that no degradation in service will result from the modernization and associated restructuring. In this report, the National Research Council's National Weather Service Modernization Committee reviews the September 1998 draft plan for MARD. The committee drew three conclusions from its review of the plan and offers five recommendations to the NWS.
Keywords: Earth Sciences

Monitoring Southern California's Coastal Waters (The National Academies Press, 1990)
Keywords: Earth Sciences

Managing Troubled Waters: The Role of Marine Environmental Monitoring (The National Academies Press, 1990)
Reports of closed beaches, restricted shellfish beds, oil spills, and ailing fisheries are some of the recent evidence that our marine environment is in trouble. More than $133 million is spent on marine environmental monitoring annually in the United States, but officials still do not have enough accurate information to make timely decisions about protecting our waters. This book presents the first comprehensive overview of marine monitoring, providing practical information and a model for revamping the nation's marine monitoring apparatus. The volume explores current monitoring programs and whether or not they work; the benefits and limitations of monitoring; the critical need for greater coordination among local, regional, and national monitoring programs; and a recommended conceptual model for developing more effective monitoring programs.
Keywords: Earth Sciences

Hurricane Elena, Gulf Coast: August 29 - September 2, 1985 - National Research Council (The National Academies Press, 1991)
Hurricane Elena, following an erratic and difficult-to-forecast course along an unusually large section of the Gulf Coast, posed special problems from New Orleans, Louisiana, to Sarasota, Florida, well before it came ashore on September 2, 1985. Considerable wind damage occurred in this area to structures that were ostensibly designed to resist such extreme wind conditions. Because similar design conditions and building control procedures exist along other U.S. hurricane-prone coasts, the conclusions drawn in this detailed book catalog the structural damage caused by the hurricane and emergency response actions, establish the wind conditions of the storm, review in-depth the building control process used in the area, and conduct necessary structural and wind tunnel tests relevant to a large number of communities along the coastal areas.
Keywords: Earth Sciences

Drought Management and Its Impact on Public Water Systems: Report on a Colloquium Sponsored by the Water Science and Technology Board - National Research Council (The National Academies Press, 1986)
Based on a colloquium sponsored by the Water Science and Technology Board, this book addresses the need for research toward the problems of water management during drought episodes. It covers such topics as the causes and occurrence of drought, drought management options, acceptable risks for public systems, and legal and institutional aspects of drought management.
Keywords: Earth Sciences

Snow Avalanche Hazards and Mitigation in the United States - National Research Council (The National Academies Press, 1990)
The present mortality as a result of snow avalanches exceeds the average mortality caused by earthquakes as well as all other forms of slope failure combined. Snow avalanches can range from small amounts of loose snow moving rapidly down a slope to slab avalanches, in which large chunks of snow break off and destroy everything in their path. Although considered a hazard in the United States since the westward expansion in the nineteenth century, in modern times snow avalanches are an increasing concern in recreational mountainous areas. However, programs for snow avalanche hazard mitigation in other countries are far ahead of those in the United States. The book identifies several steps that should be taken by the United States in order to establish guidelines for research, technology transfer, and avalanche legislation and zoning.
Keywords: Earth Sciences

Marine Structures Research Recommendations: Recommendations for the Interagency Ship Structure Committee's FY 1995 and Later-Years Research Program (The National Academies Press, 1995)
Keywords: Earth Sciences

Undersea Vehicles and National Needs - National Research Council (The National Academies Press, 1996)
The United States faces decisions requiring information about the oceans in vastly expanded scales of time and space and from oceanic sectors not accessible with the suite of tools now used by scientists and engineers. Advances in guidance and control, communications, sensors, and other technologies for undersea vehicles can provide an opportunity to understand the oceans' influence on the energy and chemical balance that sustains humankind and to manage and deliver resources from and beneath the sea. This book assesses the state of undersea vehicle technology and opportunities for vehicle applications in science and industry. It provides guidance about vehicle subsystem development priorities and describes how national research can be focused most effectively.
Keywords: Earth Sciences

International Role of U.S. Geoscience (The National Academies Press, 1987)
Keywords: Earth Sciences

Restoring and Protecting Marine Habitat: The Role of Engineering and Technology (The National Academies Press, 1994)
Tremendous changes have occurred this century in the nation's coastal habitats, in the way society views them, and in the way they are managed. This volume offers a complete, highly readable assessment of how scientific knowledge and coastal engineering capabilities can be more effectively used to protect and restore marine habitat. It addresses traditional and innovative uses of technology to protect remaining natural marine habitats, to enhance or restore those that have been altered, and to create marine habitat from lands used for other purposes. The use of dredged materials as a vital resource in protection and restoration work is explored. The book also explores organizational, management, and regulatory barriers to using the best available technology and engineering practice. Specific options for improvements are offered in each area.
Keywords: Earth Sciences

Hurricane Hugo, Puerto Rico, the Virgin Islands, and Charleston, South Carolina, September 17-22, 1989 - National Research Council (The National Academies Press, 1994)
This volume provides an account of the 1989 Hurricane Hugo for historical purposes, evaluates the physical phenomena involved and the performance of structures and systems, and identifies and recommends cases where an in-depth study would improve our ability to analyze and forecast such failures.
Keywords: Earth Sciences

Margins: A Research Initiative for Interdisciplinary Studies of the Processes Attending Lithospheric Extension and Convergence - National Research Council (The National Academies Press, 1989)
Approximately 70 percent of the world's population is concentrated in the coastal borderlands, which geologists recognize to be the present continental margins. This new book on these continental margins provides a detailed account of a meeting which brought together specialists in marine and terrestrial geology, geochemistry, and geophysics. The workshop garnered widespread support and enthusiasm for a new direction in margins research focused on interdisciplinary studies of the fundamental processes of continental margin evolution. Scientific problems and solutions were identified for both divergent and convergent margins. Results of the workshop show that many of the fundamental plate interaction processes are common to all margins, whether formed by extension, contraction, or translation. This conclusion suggests a unified approach to margins research. A margins initiative has been proposed to follow up on the workshop results by developing science programs aimed at understanding the processes that control the initiation and evolution of continental margins.
Keywords: Earth Sciences

Criteria for the Depths of Dredged Navigational Channels - National Research Council (The National Academies Press, 1983)
Keywords: Earth Sciences

Responding to Changes in Sea Level: Engineering Implications - National Research Council (The National Academies Press, 1987)
Over the last 100 years, sea level has risen approximately 12 centimeters and is expected to continue rising at an even faster rate. This situation has serious implications for human activity along our coasts. In this book, geological and coastal engineering experts examine recent sea level trends and project changes over the next 100 years, anticipating shoreline response to changing sea level and the consequences for coastal development and uses. Scenarios for future sea level rise and several case studies are presented.
Keywords: Earth Sciences